2022
DOI: 10.1111/1746-692x.12352
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Eco‐schemes in Fifteen European Union Member States

Abstract: SummaryEco‐schemes are set to play an important role in the European Union’s Common Agricultural Policy (CAP) post‐2022 for the delivery of environmental and climate benefits and enhanced animal welfare. This article surveys current plans for the design of eco‐schemes in fifteen European Union Member States. The number of eco‐scheme measures to be offered per country varies between 3 and 21, and the complexity and level of ambition of the individual measures are quite heterogeneous. The majority of the propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…Also the ECA (European Court of Auditors) reported that in the two last CAP periods (2014–2020), the CO 2 emissions originating from the farming sector have not been curbed, despite expenditures beyond €100 million attributed to climate action (ECA, 2021). For example, (i) the rural development programme is still applied to improve drainage systems, although it is known to further degrade farmland (Thorsøe et al, 2022); (ii) the installation of drip irrigation on sloping land is still subsidized while this induces massive erosion problems (Hondebrink et al, 2017); and soil degradation (Puy et al, 2017) and (iii) the proposed eco‐schemes under the forthcoming CAP strategic plans will likely be insufficient to alter the course for European farmers (Hasler et al, 2022; Runge et al, 2022). Therefore, developing novel payment schemes facilitating behavioural change and perception of the farmers in a co‐creative way is essential, as the uptake of sustainable practices is much more efficient if the farmers agree to the management change (Cerdà et al, 2019).…”
Section: Discussion: Key Research Foci and Approaches For Realizing T...mentioning
confidence: 99%
“…Also the ECA (European Court of Auditors) reported that in the two last CAP periods (2014–2020), the CO 2 emissions originating from the farming sector have not been curbed, despite expenditures beyond €100 million attributed to climate action (ECA, 2021). For example, (i) the rural development programme is still applied to improve drainage systems, although it is known to further degrade farmland (Thorsøe et al, 2022); (ii) the installation of drip irrigation on sloping land is still subsidized while this induces massive erosion problems (Hondebrink et al, 2017); and soil degradation (Puy et al, 2017) and (iii) the proposed eco‐schemes under the forthcoming CAP strategic plans will likely be insufficient to alter the course for European farmers (Hasler et al, 2022; Runge et al, 2022). Therefore, developing novel payment schemes facilitating behavioural change and perception of the farmers in a co‐creative way is essential, as the uptake of sustainable practices is much more efficient if the farmers agree to the management change (Cerdà et al, 2019).…”
Section: Discussion: Key Research Foci and Approaches For Realizing T...mentioning
confidence: 99%
“…Within the EU's Common Agricultural Policy, there are ongoing debates and revisions with respect to restructuring the budgetary allocations and thus the conditions under which payments are issued (Runge et al., 2022). The post‐2020 CAP reform seeks to provide farm income support, conditional on respecting specific environmental standards.…”
Section: Discussionmentioning
confidence: 99%
“…Both price premiums and agri-environmental schemes can compensate farmers for adopting low pesticide use practices and the associated changes in yields, costs, and risks. For example, Germany and Switzerland have introduced agri-environmental schemes that compensate farmers for reducing or avoiding pesticide use (Mack et al, 2023;Runge et al, 2022). In view of all these factors, the overall impact on farm incomes is unclear and is likely to be farm-specific.…”
Section: Stricter Pesticide Policies Are Affecting Farmsmentioning
confidence: 99%